K E D U D U K A N B A D A N K E P E G A W A I A N N E G A R A S E B A G A I L E M B A G A P E N G E L O L A K E P E G A W A I A N M E N U R U T U N D A N G – U N D A N G N O M O R 5 T A H U N 2 0 1 4 T E N T A N G A P A R A T U R S I P I L N E G A R A - Tri Putra Dewi, Desak Nyoman; Keneng, I Ketut (Kertha Negara : Journal Ilmu Hukum; Vol. 04, No. 02, Februari 2016, 2016)
U n d a n g – U n d a n g N o m o r 5 T a h u n 2 0 1 4 t e n t a n g A p a r a t u r S i p i l N e g a r a m e r u p a k a n d a s a r u n t u k m e l a k s a n a k a n t u g a s d a n f u n g s i u t a m a s e b a g a i p e g a w a i n e g e r i a t a u u n t u k m e n j a m i n k e l a n c a r a n p e n y e l e n g g a r a a n , k e b i j a k a n m a n e j e m e n p e g a w a i n e g e r i . T e r d a p a t p e r m a s a l a h a n y a i t u B a g a i m a n a k a h k e d u d u k a n B a d a n K e p e g a w a i a n N e g a r a p a s c a d i u n d a n g k a n n y a U n d a n g – u n d a n g N o m o r 5 T a h u n 2 0 1 4 t e n t a n g A p a r a t u r S i p i l N e g a r a . M e t o d e y a n g d i g u n a k a n a d a l a h m e t o d e p e n e l i t i a n n o r m a t i f . D a l a m P a s a l 4 7 U n d a n g – U n d a n g N o m o r 5 T a h u n 2 0 1 4 d a n P e r a t u r a n P r e s i d e n N o m o r 5 8 T a h u n 2 0 1 3 y a n g m e n g a t u r T e n t a n g B a d a n K e p e g a w a i a n N e g a r a . P e r a t u r a n i n i d i k e l u a r k a n u n t u k m e n d u k u n g e f e k t i v i t a s s e r t a e f i s i e n s i p e l a k s a n a a n t u g a s d a n f u n g s i B a d a n K e p e g a w a i a n . K e b e r a d a a n B a d a n K e p e g a w a i a n N e g a r a s e c a r a e k s p l i s i t d i j e l a s k a n d a l a m U n d a n g – u n d a n g N o m o r 5 T a h u n 2 0 1 4 d a n k e d u d u k a n B a d a n K e p e g a w a i a n N e g a r a t e r d a p a t d a l a m P e r a t u r a n P r e s i d e n N o m o r 5 8 T a h u n 2 0 1 3 . U n t u k b a t a s a n k e r j a t i d a k d i a t u r d a l a m U n d a n g – u n d a n g N o m o r 5 T a h u n 2 0 1 4 d a n P e r a t u r a n P r e s i d e n N o m o r 5 8 T a h u n 2 0 1 3 .
Keywords: B a d a n K e p e g a w a i a n , P e g a w a i N e g e r i , P e l a y a n a n P u b l i k , M a n e j e m e n